DE L’IRRESPONSABILITE PENALE DES ANCIENS CHEFS D’ETAT ET DE GOUVERNEMENT CONGOLAIS POUR DES FAITS COMMIS DURANT LEURS MANDATS : UN RECUL DANS LA LUTTE CONTRE L’IMPUNITE - Kausa, Kakule (IJRDO - Journal of Social Science and Humanities Research, 2022)
This study aims   to demonstrate that the will of the primary sovereign, that of consecrating the repression of criminal acts that a head of State or a prime Minister may commit during their mandate, is intentionally broken by the legislator and by the constitutional judge who shamelessly seek to create an artificial corridor of impunity in favor of the said authorities when they get out of their functions. She denounces this politico-judicial cheating and pleads for the fight against impunity for crimes, whoever the perpetrator.Kee words:   former head of state, former prime minister, privilege of jurisdiction, criminal responsibility, criminal non-responsibility.